Dinamika Perusahaan Semarang-Joana Stoomtram Maatschappij (SJS): Jejak Kereta Api di Pulau Jawa Tahun 1881-1900 - Cahya Adhitya Pratama Cahya; Gery Erlangga Gery (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
The implementation of the forced cultivation policy in the Dutch East Indies has provided significant changes such as the transition of transportation facilities. This spearheaded the development of railways on the island of Java, one of which was the creation of the Semarang-Juwana railway line built by the Semarang-Joana Stoomtram Maatchappij (SJS) company. So this study aims to analyze the history and development of the Semarang-Juwana railway line built by the Semarang-Joana Stoomtram Maatschappij (SJS) company. This research uses a historical method consisting of four steps, namely heuristics, source criticism, interpretation and historiography. The results showed that the presence of the Semarang-Juwana line has also indirectly had an impact on the growth of the area around the train line which is characterized by increasing community mobility and increasing the pace of economic activity of indigenous peoples.